A Morphometric Study of Lumbar Spine Pedicles in Nepalese Population - Marasini, Rudra Prasad; Gautam, Pratiksha; Sherchan, Binod; Gurung, Ganesh; K.C., Bachchu Ram (Journal of College of Medical Sciences-Nepal, 2015)
Background and Objective: In this observational study, morphometric data were obtained and analyzed by taking plain x-rays in various age groups to establish the morphometric values in Nepalese population. Methods: All the pedicle dimensions were measured by taking plain x-ray AP (Antero-posterior) and Lateral view of the lumbar spine in 246 Nepalese of different age groups. Pedicle diameters (Vertical and Horizontal) and interpedicular distance were measured in AP radiographs and sagittal angle was measured in the lateral radiographs. Differences between mean dimensions of pedicles of male and female of various age groups were tested by using ANOVA, independent t-test was used to test the individual mean dimensions. Results: Mean values of the pedicle dimensions were found as: Horizontal diameter (L1=7.17mm, L2=7.26mm, L3= 9.50mm, L4= 10.57mm and L5=11.3mm), Vertical diameter (L1= 15.00mm, L2=15.28mm, L3=15.21mm, L4=13.44mm and L5= 12.59mm), Interpedicular distance (L1= 25.54mm, L2 =27.03mm, L3 = 27.70mm, L4 =28.62mm and L5= 31.29mm) and the sagittal angle (L1=17.83degree, L2=15.7degree, L3= 15.91degree, L4=13.94degree, and L5=12.97degree) respectively. Conclusions: Values of pedicle dimensions found in Nepalese population by this study can be guidelines for the transpedicular procedure and for further research activities. JCMS Nepal 2014; 10(4):12-17